Zn-doped etch-and-rinse model dentin adhesives: Dentin bond integrity, biocompatibility, and properties - Barcellos, Daphne Câmara [UNESP]; Fonseca, Beatriz Maria [UNESP]; Pucci, César Rogério [UNESP]; Cavalcanti, Bruno Das Neves; Persici, Erasmo De Souza; De Paiva Gonçalves, Sérgio Eduardo [UNESP] (Elsevier, 2016)
Objective This study assessed a 6 month resin/dentin bond's durability and cytotoxic effect of Zn-doped model dentin adhesives. The mechanical and physicochemical properties were also tested. Methods A model etch-and-rinse single-bottle adhesive was formulated (55 wt.% Bis-GMA, 45 wt.% HEMA, 0.5 wt.% CQ, 0.5 wt.% DMAEMA) and Zinc methacrylate (Zn-Mt) or ZnO nanoparticles (ZnOn) were added to the model's adhesive, resulting in three groups: Group Control (control model adhesive); Group Zn-Mt (1 wt.% Zn-Mt incorporated to adhesive) and Group ZnOn (1 wt.% ZnOn incorporated to adhesive). The microtensile bond strength (mTBS) was assessed after 24 h or 6 months in water storage. Mechanical properties (diametral tensile strength/DTS, flexural strength/FS, flexural modulus/FM, resilience modulus/RM, and compressive strength/CS) and physicochemical properties (polymerization shrinkage/PS, contact angle/CA, water sorption/WS, and water solubility/WS) were also tested. Cytotoxicity was evaluated with SRB biochemical assay. Results No significant difference in the DTS, FS, FM, CS, CA, WS, and WS were found when 1% of ZnOn or Zn-Mt was added to the model dentin adhesive. Group Zn-Mt decreased the RM of adhesive. Groups Zn-Mt and ZnOn decreased the PS of adhesives. Group ZnOn reduced the cytotoxicity of adhesive. Group ZnOn preserved mTBS after 6 months storage without degradation areas as seen by SEM analysis. Significance The 1 wt.% ZnOn may preserve the integrity of the hybrid layer and may reduce cytotoxicity and polymerization shrinkage of model dentin adhesive. The addition of Zn-Mt to the adhesive had no beneficial effects.
Keywords: Collagen; Dental adhesive; Dentin-bond agents; Matrix metalloproteinase inhibitors; Methacrylates; Zinc oxide